PROGRAM INCOME GENERATION DALAM MENGEMBANGKAN KREDIT MIKRO PADA RUMAH TANGGA NELAYAN MISKIN DI KELURAHAN PASIE NAN TIGO, KECAMATAN KOTO TANGAH, PADANG - Sesi, Sesi; Indraddin, Indraddin; Maihasni, Maihasni (JISPO Jurnal Ilmu Sosial dan Ilmu Politik, 2019)
Fishermen in the Pasie Nan Tigo Village, Padang City are generally poor. Various efforts to improve the economic condition of fishermen in the Pasie Nan Tigo sub-district have been carried out by both the Government and the private sector to reduce poverty in fishermen families. One program is the assistance of capital loans for business development given to fishing communities carried out by the Indonesian Conscience Foundation. Recorded as of October 31, 2017 there were as many as 20 groups that had received assistance with the business development capital loan. But on the loan repayment process, from the 20 groups that received the loan for business development capital loans from the GNI, there were 8 groups that paid installments for microcredit installments, and there were 12 other groups who did not pay micro credit installments. This research gave attention to 20 groups conveying the factors causing group members to pay micro credit installments.